IbM Kelompok Usaha Sirup Belimbing Wuluh Cap "Kendi" di Kecamatan Genteng Kota Surabaya - Indah Murti; D. Jupriono; Istantyo Yuwono (JPM17: Jurnal Pengabdian Masyarakat, 2014)
Abstract.Â Medicine plants have become cultural heritage of traditional medication which are known since the past time and conserved hereditary. Meanwhile all of those plants have not been processed and used optimally; only some processes have been used. Blimbing wuluh process is relatively new developed especially by Tani Candirejo Group at Genteng Subdistrict. Blimbling wuluh syrup marketing is still limited on bazar and exhibitions, or orders from consumers. Likewise the production process is still done very manually, moreover the uninteresting package. The performance of blimbing wuluh beverage along this time is with plastic glass and non-permanently cup, or syrup in bottle without seal. This condition is less desired by consumers. Besides, not all of these small enterprises apply accountancy or entrepreneur noting. Small enterprise access and horizon in making use of market is also still lacking. Based on these problems, the solutions offered and agreed together are supplyings of semiautomatic cup sealer machine, metal and plastic screw bottle cup machine, and semiautomatic seal tool, increasing of medicine plant process production (belimbing wuluh, seasons, and rosella), increasing of capabilities in entrepreneur management and marketing strategy, and training of orderly accountancy and entrepreneur noting. The methods of training and accompaniment are done through Learning By Doing, and Participative Method.Â Key words: production process, package, marketing strategy, accountancy and entrepreneur noting